Modelling amyotrophic lateral sclerosis in mice. (2017) - Stephenson, Jodie; Amor, Sandra
Abstract : Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disease for which there is limited treatment. Riluzole, that extends life by several months, has been the only ALS drug for 22 years until the recent FDA approval of Edaravone. Despite many promising compounds identified in preclinical studies in the SOD1 G93A mouse model, few have translated to the clinic. The failure to translate therapies in animals to people with ALS has questioned the validity of the SOD1 G93A mouse model, especially since these mutations are only present in 1–2% of people with ALS. Here, we review the mouse models that are key for drug development in ALS. The key features of each genetic subgroup are discussed and the models are compared. We also propose how the models could be further developed to better model ALS and thus more effectively advance ALS drug discovery. We recommend the use of a wider range of ALS mouse models in drug development to represent the broader ALS population and subgroups.